Long‐Term Outcomes Among Participants in the WEGENT Trial of Remission‐Maintenance Therapy for Granulomatosis With Polyangiitis (Wegener's) or Microscopic Polyangiitis. Issue 3 (March 2016) - Puéchal, Xavier; Pagnoux, Christian; Perrodeau, Élodie; Hamidou, Mohamed; Boffa, Jean‐Jacques; Kyndt, Xavier; Lifermann, François; Papo, Thomas; Merrien, Dominique; Smail, Amar; Delaval, Philippe; Hanrotel‐Saliou, Catherine; et al.
Abstract : Objective: Findings from the WEGENT trial and other short‐term studies have suggested that azathioprine (AZA) or methotrexate (MTX) could effectively maintain remission of granulomatosis with polyangiitis (Wegener's) (GPA) or microscopic polyangiitis (MPA). This study was undertaken to examine whether differences in rates of relapse or adverse events would appear after discontinuation of these 2 maintenance regimens, when assessed over a longer followup period. Methods: Long‐term outcomes in patients enrolled in the WEGENT trial were analyzed according to their randomized treatment group (AZA or MTX). Parameters at trial entry were evaluated as potential prognostic factors for death, relapse, or damage in multivariate models. Results: Data from 10 years of followup were available for 112 (88.8%) of the 126 original trial participants. The median followup time was 11.9 years (95% confidence interval [95% CI] 11.3–12.5 years). In patients receiving AZA and those receiving MTX, the 10‐year overall survival rates were 75.1% (95% CI 64.8–86.9%) and 79.9% (95% CI 70.3–90.8%) ( P = 0.56), respectively, and relapse‐free survival rates were 26.3% (95% CI 17.3–40.1%) and 33.5% (95% CI 23.5–47.7%) ( P = 0.29), respectively. No between‐treatment differences were observed with regard to rates of relapse, adverse events, damage, survival without severe side effects, and survival without relapse and severe side effects. In analyses limited to the 97 patients with GPA, no between‐treatment differences in survival rates were observed. The 10‐year relapse‐free survival rate was lower in patients with GPA than in patients with MPA. However, in the multivariate analysis, anti–proteinase 3 antineutrophil cytoplasmic antibody (ANCA) positivity, and not GPA, was retained as being independently associated with the relapse rate. Conclusion: The results of this long‐term analysis confirm that AZA and MTX are comparable treatment options for maintaining remission of GPA or MPA. Despite achieving good overall survival with these treatments, relapse rates, adverse events, and damage remain matters of concern and further studies are needed to reduce their frequency in these ANCA‐associated vasculitides.